STRATEGI BAURAN PEMASARAN PELAYANAN KESEHATAN RUMAH SAKIT YADIKA PONDOK BAMBU PADA MASA PANDEMI COVID-19 - Septian Ekawati; Helen Andriani (Yayasan Pendidikan Medika Indonesia, 2022)
The Covid-19 pandemic has an impact on changes in consumer behavior that affect organizational operations, including hospital organizations. The impact on non-COVID-19 referral hospitals can be seen from the decline in the number of outpatient visits and inpatient care for non-Covid-19 patients. This can lead to reduced income and affect the hospital's cash flow. This study aims to determine the marketing mix strategy of health services carried out at the Yadika Pondok Bambu Hospital during the Covid-19 pandemic. The research was conducted using a qualitative approach method through interviews with hospital’s managements involved in determining marketing strategies and being responsible for marketing hospital health services during the Covid-19 pandemic by assessing aspects of the marketing mix consisting of product, price, promotion, place, people, process, and physical facility. The results show that hospitals maintain the quality of existing services by adding new services needed by the community during the pandemic, revising service rates to become more affordable, increasing promotion of hospital health service products by utilizing electronic media, especially social media, increasing access to health services by telemedicine, improving employee competence, conducting health screening and Covid-19 screening for employees, perfecting the referral process flow and patient service process flow including shortening waiting times, and making improvements to existing service facilities according to service standards during the Covid-19 pandemic.